Renewable energies in cities: Perspectives for the use of biogas in Brazil - Neres, Letícia Morais; Ramos, Heidy Rodriguez (Electronic Journal "Fórum Ambiental da Alta Paulista", 2022)
One of the main challenges for the present and future of citiesare new energy sources that allow good efficiency and low environmental impact. In this sense, this study analyzed biogas, an energy source from the decomposition of organic matter. A theoretical essay was carried out from bibliographical research, with the aim of presenting the current scenario of the different perspectives of production and application of biogas in Brazil, in urban and rural areas of the country. The observed results showed that, in rural areas, the input for the production of biogas comes mainly from animal husbandry, and that the form of use is mainly directed towards obtaining thermal energy. In urban areas, practically all biogas production is carried out in sanitary landfills and sewage treatment plants, given the large amount of excess organic matter from the waste treatment activity. However, even though the country has relatively important indices of biogas production and use, it was clear from the theoretical framework analyzed that not only is the amount generated very low for generation potentials in Brazil, but there is also an evident lack of technologies in relation to biodigesters, in addition to a weak legislation to promote Brazilian biogas, which led to the conclusion that biogas production in the country is proceeding at a very slow pace. The study is limited in terms of detailing the barriers observed, and, therefore, it is suggested that future studies seek an in-depth analysis of these barriers.